Public health is Indigenous: design and launch of the NW NARCH research academy for American Indian high school students - Ghost Dog, Celena; Kakuska, Amanda; Rushing, Stephanie Craig; Cunningham, Grazia; Kelley, Allyson (Frontiers in Public Health, 2025)
This article describes the collaborative process of designing the Northwest Native American Research Center for Health (NW NARCH) Research Academy. We describe the NW NARCH partnership-building process with federally recognized tribes in the United States, Washington, Oregon, and Idaho while outlining the goals and steps to indigenize the curriculum. The Research Academy curriculum utilized socioecological models and theoretical frameworks informed by indigenous pedagogies, like the Circle of Courage to further students’ sense of belonging, mastery, independence, and generosity. NW NARCH recruited four sites in 2023 with tribal representation across the Pacific NW. From October 2023 to April 2024, NW NARCH delivered 11 virtual (live) sessions. Our evaluation of the Research Academy included a student-driven evaluation plan, a visual logic model, student and mentor surveys, and Canvas (online learning platform) page views. Preliminary findings and lessons learned from the first cohort of Research Academy students demonstrate that NW NARCH successfully built a public health pathways program for American Indian and Alaska Native students. The Research Academy successfully connected AI/AN high school students to relatable public health role models from a variety of professional pathways, including university professors and Tribal Epidemiology Center staff. Lessons from this first year of the NW NARCH underscore the importance of community- research collaborations and equity-focused programming for underrepresented racial /ethnic groups.